Upaya Mengatasi Kedisiplinan Siswa di Lingkungan PAUD: Effective Strategies in Overcoming Student Discipline Problems in Early Childhood Education (PAUD) Environment - Siti Nurma; Gilar Gandana; Risbon Sianturi (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
Facing general challenges in early childhood education (PAUD), especially related to student discipline problems, is the main focus that professional teachers must pay attention to. One crucial aspect is a deep understanding of student behavior management. Effective handling of this problem requires the right approach to ensure a smooth learning process. Discipline education in early childhood involves a clear understanding of the difference between behavior that is considered positive and negative. In this context, the approach to instilling discipline at an early age must be carried out in a friendly manner and through play interactions. The role of teachers, society and parents is very important in forming and teaching the values ​​of discipline to children. This article aims to present several effective strategies for dealing with student discipline problems in PAUD. Teachers need to have skills in managing the classroom well to create a dynamic and effective learning environment, considering that there are students with diverse backgrounds. The teacher’s role is very crucial in solving student discipline problems because discipline is the key to success in all things. From this discipline, a consistent attitude will emerge in upholding principles, perseverance in business, strong in defending the truth, and never giving up. Therefore, this article will discuss various practical strategies that can help PAUD educators face and overcome challenges in maintaining student discipline.   ABSTRAK Menghadapi tantangan umum di dalam pendidikan anak usia dini (PAUD) terutama berkaitan dengan masalah disiplin siswa, merupakan fokus utama yang harus diperhatikan oleh guru-guru yang profesional. Salah satu aspek krusial adalah pemahaman yang mendalam mengenai manajemen perilaku siswa. Penanganan yang efektif terhadap masalah ini memerlukan pendekatan yang tepat guna memastikan kelancaran proses pembelajaran. Pendidikan disiplin pada anak-anak usia dini melibatkan pemahaman yang jelas tentang perbedaan antara perilaku yang dianggap positif dan negatif. Dalam konteks ini, pendekatan untuk menanamkan disiplin pada usia dini harus dilakukan secara ramah dan melalui interaksi bermain. Peran guru, masyarakat, dan orangtua sangatlah penting dalam membentuk dan mengajarkan nilai-nilai disiplin kepada anak-anak. Artikel ini bertujuan untuk menyajikan beberapa strategi efektif dalam menangani masalah disiplin siswa di PAUD. Guru perlu memiliki keterampilan dalam mengelola kelas dengan baik untuk menciptakan lingkungan belajar yang dinamis dan efektif, mengingat adanya siswa dengan latar belakang yang beragam. Peran guru sangatlah krusial dalam menyelesaikan masalah disiplin siswa karena disiplin merupakan kunci kesuksesan dalam segala hal. Dari disiplin tersebut, akan timbul sikap konsisten dalam memegang prinsip, tekun dalam usaha, kuat dalam membela kebenaran, dan tidak mengenal kata menyerah. Oleh karena itu, artikel ini akan membahas berbagai strategi praktis yang dapat membantu pendidik PAUD menghadapi serta mengatasi tantangan dalam menjaga disiplin siswa.